Genetic resistance of pear cultivars to fire blight (International Journal of Biology and Chemistry, 2023)
The economic damage accompanying the fire blight is expressed both in the loss of crops and in the costs associated with uprooting of infected trees and restoration of fruit plantations.  Pear is characterized the highest rates of susceptibility to fire blight. Development of genetically resistant cultivars is one of the crucial aspects of managing fire blight, which would allow foregoing the current economically or ecologically unsound methods such as removal of infected plants or application of antibiotics on the early stages of development. In this research, a five-year monitoring of the distribution of fire blight was performed among a collection of pear cultivars growing in a pomological garden. The cultivars ‘Ajdana’ and ‘Kirgizskaya zimnyaya’ showed the highest resistance to E. amylovora according to the results of field inspections. The infection occasions for every cultivar were confirmed by direct or indirect PCR. ‘Ajdana’ and ‘Kirgizskaya zimnyaya’ bear alleles of fire blight resistance for the CH02F06 marker, and ‘Kirgizskaya zimnyaya’ additionaly carries the resistance allele for the TsuENH017 marker. ‘Talgarskaya krasavica’ and ‘Lesnaya Krasavitsa’ are susceptible cultivars to fire blight, but at the same time their genomes include the resistance alleles for the CH02F06 marker.